2011
DOI: 10.1080/12538078.2011.10516300
|View full text |Cite
|
Sign up to set email alerts
|

Effets de quelques prétraitements physico—chimiques sur la levée de l'inhibition tégumentaire des graines deRetama monospermaBoiss. et recherches des conditions thermiques optimales de germination

Abstract: Résumé.-Les graines de Retama monosperma sont affectées d'une inhibition tégumentaire qui empêche leur germination dans les conditions naturelles. Au laboratoire, cette germination est déclenchée après scarification chimique des graines par l'acide sulfurique pur, dans une gamme de températures se situant entre 10 °C et 30 °C. L'analyse en composantes principales des données relatives aux capacités de germination, aux coefficients de vélocité et aux temps de latence obtenus, après prétraitement à l'acide sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Our results join those of Bouredja et al [20], which indicate that the optimal temperature of the germination of Retama monosperma seeds is 20 °C, while at the temperatures 5 °C, 35 °C and 40 °C, the germination weakens.…”
Section: J Fundam Appl Sci 2017 9(3) 1284-1299 1289supporting
confidence: 79%
See 1 more Smart Citation
“…Our results join those of Bouredja et al [20], which indicate that the optimal temperature of the germination of Retama monosperma seeds is 20 °C, while at the temperatures 5 °C, 35 °C and 40 °C, the germination weakens.…”
Section: J Fundam Appl Sci 2017 9(3) 1284-1299 1289supporting
confidence: 79%
“…In addition, currently the lack of information about the physiology of germination of R. raetam seeds, the hardness of its coats and their impermeability to water and oxygen seem to be in the same case as many other Fabaceae [18,19,20], those are the essential causes of the absence of such way of regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats obtenus, sont similaires à celles décrits par JAOUADI et al (2010) pour les graines d'Acacia tortilis [14]. Cependant, des traitements similaires sur une fabacée Retama monosperma (trempage des graines dans l'acide sulfurique pendant 1, 2 et 3 heures), n'ont permis aucune amélioration des taux de germination [16]. La durée optimale de trempage parait être en rapport avec la dureté des téguments [17].…”
Section: -Discussionunclassified
“…This confirms the results of our previous studies (Kheloufi et al, 2018a;Kheloufi et al, 2019), indicating that the unscarified seeds of leguminous trees do not show imbibition or germination due to the seed coat rigidity. A number of studies on breaking the seed coat dormancy in leguminous species have shown that chemical scarification by concentrated sulphuric acid results in very high germination levels, compared to scarification by boiling water or sandpaper (especially in the instance of a large seed batch of Retama monosperma (Bouredja et al, 2011), Retama raetam (Mehdadi et al, 2017), Astragalus armatus (Kheloufi et al, 2018b) and several Acacia species (Kheloufi et al, 2019). The second advantage of sulphuric acid immersion is that it can be reused 2 or 3 times with the same benefits.…”
Section: Breaking Seed Coat Dormancy In R Sphaerocarpamentioning
confidence: 99%